Reflections Based on the Latest 3D Films: The Development and Challenges of the Contemporary Chinese Animation Industry - Liang, Li (International Journal of Academic Research in Progressive Education and Development, 2023)
This paper takes several recently successful Chinese 3D animation films as examples to discuss the application of 3D technology in the development of contemporary Chinese animation and its role in China's animation industry. The paper analyzes from the perspectives of technology, art and industry, and points out that the application of 3D technology is an inevitable trend in the development of China's animation industry. At the same time, this paper also explains the problems and challenges in the development of 3D animation in China, including technical bottlenecks, creative styles and content innovation. Finally, this paper looks forward to the future development of 3D animation in China and puts forward relevant suggestions.